Analisa Faktor Ibu dengan Kejadian Bayi BBLR di Puskesmas Situbondo: Studi Data Register Kohort Tahun 2020: Analysis of Maternal Factors with the Incidence of LBW Infants at Situbondo Health Center: Study of Cohort Register Data in 2020 - Widowati, Nurihza; Ningtyias, Farida Wahyu; Sulistiyani, Sulistiyani (Universitas Airlangga, 2024)
Background: Infant mortality rate (IMR), especially in the perinatal period, is caused by the condition of low-birth-weight babies (LBW). The nutritional and health conditions of pregnant women play an important role in determining the nutritional status of infants starting during pregnancy. Maternal factors are one of the causes of LBW in infants. Objectives: Analyzing maternal factors (parity, Hemoglobin (Hb) level of the mother during pregnancy, age of the mother during pregnancy, nutritional status of the mother during pregnancy (chronic energy deficiency = KEK), and the distance between pregnancies that cause the incidence of LBW babies at the Situbondo Health Center in 2020. Methods: The case-control method was used in this study by using cohort register data at the Situbondo Health Center. In March 2022, data were collected from 82 mothers including 41 mothers of LBW babies as a case group and 41 mothers of the control group who did not have LBW babies. Data were analyzed using chi-square test. Results: The results proved that maternal hemoglobin level was associated with the incidence of LBW babies (p=0.026; OR=3.088; 95%; CI=1.240-7.692). However, the variables of parity, maternal age during pregnancy, maternal nutritional status (SEZ), and pregnancy distance were not associated with the incidence of LBW babies. Conclusions: Low Hb levels in pregnant women have a higher risk of delivering LBW babies. It is recommended that pregnancy checks be carried out by pregnant women regularly at least 6 visits to health facilities and it is recommended to take blood supplement tablets regularly, eat healthy foods and do not believe in myths that are detrimental to the health of pregnant women.